EXTRACELLULAR MATRIX OF RAT LIVER UNDER THE CONDITIONS OF COMBINING SYSTEMIC INFLAMMATORY RESPONSE SYNDROME AND CHRONIC ALCOHOL INTOXICATION - Mykytenko, A.O.; Akimov, O.Ye.; Yeroshenko, G.A.; Neporada, K.S. (World of Medicine and Biology, 2022)
The extracellular matrix of the liver is a highly dynamic structure that undergoes constant controlled remodeling to maintain homeostasis and suffers from changes during the development of pathological processes. The aim of this study was to establish the effect of systemic inflammatory response syndrome on the background of chronic alcohol intoxication on the concentration of oxyproline, glycosaminoglycans and sialic acids in the liver of rats. The study was performed on 24 male Wistar rats. Animals were divided into 4 groups of 6 animals: I – control; II – systemic inflammatory response syndrome group; III – alcoholic hepatitis group and IV – animals with a combination of systemic inflammatory response syndrome and chronic alcohol intoxication. The concentrations of glycosaminoglycans, heparin-heparan, keratan-dermatan and chondroitin fractions of glycosaminoglycans, free oxyproline and sialic acids were studied in the liver tissue homogenate. The combination of systemic inflammatory response syndrome and chronic alcohol intoxication leads to increased intensity of collagenolysis, glycoprotein catabolism and reduced intensity of breakdown of proteoglycans of connective tissue of the liver. However, it changes the ratio of individual fractions of glycosaminoglycans in the direction of reducing the concentration of anti-inflammatory and increasing regenerative.
Keywords: liver; alcoholic hepatitis; oxyproline; glycosaminoglycans; sialic acids